1998
DOI: 10.1161/01.atv.18.6.947
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Diabetes and Hypertension on Determinants of Endothelial Adhesiveness

Abstract: Abstract-Epidemiological studies have established that diabetes mellitus and hypertension are independent risk factors for atherosclerosis. One of the earliest abnormalities seen in atherogenesis is enhanced monocyte adherence to the endothelium. The mechanisms by which diabetes mellitus or hypertension enhances monocyte-endothelial cell interactions are incompletely characterized. It is not known whether there are additive interactions between these risk factors on endothelial adhesiveness for monocytes. Male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 61 publications
1
33
3
Order By: Relevance
“…These adhesion molecules include E-selectin, which is produced by endothelial cells, and P-selectin, which is a product of both endothelial cells and platelets, 51 and a relation to adhesive molecules has previously been reported in some hypertensive patients. [52][53][54][55] In the present study, we found that Eselectin levels were significantly increased in the hypertension patients with diabetes. An increase in activated platelets and PDMPs, leading to monocyte infiltration of the arterial wall, has been suggested to be important in the development of atheroscler-osis.…”
Section: Discussionsupporting
confidence: 62%
“…These adhesion molecules include E-selectin, which is produced by endothelial cells, and P-selectin, which is a product of both endothelial cells and platelets, 51 and a relation to adhesive molecules has previously been reported in some hypertensive patients. [52][53][54][55] In the present study, we found that Eselectin levels were significantly increased in the hypertension patients with diabetes. An increase in activated platelets and PDMPs, leading to monocyte infiltration of the arterial wall, has been suggested to be important in the development of atheroscler-osis.…”
Section: Discussionsupporting
confidence: 62%
“…These in vivo studies have revealed that several ACE inhibitory peptides, including two caseinderived tripeptides, IPP and VPP, significantly reduce high blood pressure 3,33) . In light of monocyte-endothelial cell interaction, previous studies demonstrated that thoracic aorta from SHR bind monocytic cells with greater activity than aorta from normotensive Wistar-Kyoto rats 34) . Although the inhibitory effect of ACE inhibitors on in vivo monocyte adhesion to endothelium also has not been reported, the VPP peptide, having an antihypertensive effect on SHR, might affect monocyteendothelial cell interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic susceptibility and environmental factors, including poor nutrition, obesity, and lack of physical activity, also play a significant role in developing CVD. [19][20][21][22] Mature adipocytes produce several adipokines (proinflammatory mediators), including C-reactive protein (CRP), interleukin-6, tumor necrosis factor-alpha (α), visfatin, leptin, resistin, angiotensinogen, and plasminogen activator inhibitor-1 (PAI-1), that are associated with developing CVD. 23 Research has shown that circulating levels of several adipokines are elevated in obese and insulin-resistant states.…”
Section: S Ss S Pathogenesis Of Cardiovascular Diseasementioning
confidence: 99%